2016
DOI: 10.1002/jrs.4983
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional Raman spectroscopy study of ionogel phase formation in long‐chain ionic liquid/water systems

Abstract: The phase behavior of the imidazolium‐based room temperature ionic liquids (RTILs) 1‐decyl‐3‐methyl‐imidazolium bromide and chloride ([C10mim][Br], [C10mim][Cl]) were studied by 2D Raman correlation spectroscopy and principal component analysis. The hydrogen‐bonded network changes and the liquid crystalline ionogel phase formation were observed when water content was continuously increased in the system, and the Raman shift of C–H stretching modes in spectra was monitored. The extent of liquid crystalline iono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In particular, C 10 mimCl is reported to present unique self-assembly characteristics [ 23 ]. Moreover, a water content above 3% w/w can promote a H-bonded network and liquid crystalline gel phase with C 10 mimCl [ 26 ], which is the case in our work (water content 6.9% w/w). The C 10 HC gel presented a surface topography of stripes but with a higher RMS roughness (3.2 ​nm) when compared to C 10 F. These results suggest that the IL self-assembling properties are predominant in the final hierarchical order of the fibroin ionogel, and that fibroin affects the organization of the IL creating smaller ordered clusters, suggesting that fibroin chains are interspersed in the IL supramolecular assemblies.…”
Section: Resultsmentioning
confidence: 74%
“…In particular, C 10 mimCl is reported to present unique self-assembly characteristics [ 23 ]. Moreover, a water content above 3% w/w can promote a H-bonded network and liquid crystalline gel phase with C 10 mimCl [ 26 ], which is the case in our work (water content 6.9% w/w). The C 10 HC gel presented a surface topography of stripes but with a higher RMS roughness (3.2 ​nm) when compared to C 10 F. These results suggest that the IL self-assembling properties are predominant in the final hierarchical order of the fibroin ionogel, and that fibroin affects the organization of the IL creating smaller ordered clusters, suggesting that fibroin chains are interspersed in the IL supramolecular assemblies.…”
Section: Resultsmentioning
confidence: 74%
“…Raman spectroscopy is also used to study the unprecedented enhancement of water content of hydrophobic IL when mixed with zwitterion [ 11 ] and the state of the water molecules in liquid crystalline ion‐gel phase in IL/water mixtures. [ 12,13 ] Recently, it has been shown that Raman spectroscopy is useful to study the enhancement of CO 2 capture in IL/water binary mixtures. [ 14 ]…”
Section: Introductionsmentioning
confidence: 99%
“…[1] Raman spectroscopy is also used to study the unprecedented enhancement of water content of hydrophobic IL when mixed with zwitterion [11] and the state of the water molecules in liquid crystalline ion-gel phase in IL/water mixtures. [12,13] Recently, it has been shown that Raman spectroscopy is useful to study the enhancement of CO 2 capture in IL/water binary mixtures. [14] In this short review, we have not covered the Raman studies of just ILs (cation and anion) and DFT of ILs as there are some excellent recent reviews that are available on these topics.…”
Section: Introductionsmentioning
confidence: 99%
“…Kausteklis, Balevicius, and Aleksa carried out a two‐dimensional Raman study of ionogel phase formation in long‐chain ionic liquid/water systems. Their hypothesis of weaker hydrogen bonds involving the C(4)H and C(5)H groups and stronger hydrogen bonds of the C(2) H groups was supported by Raman results . Lou et al described a simple drop‐and‐detect method using porous alumina ceramics as platforms for rapid SERS spectroscopy.…”
Section: Raman Techniques and Methodsmentioning
confidence: 99%
“…Their hypothesis of weaker hydrogen bonds involving the C(4)-H and C(5)-H groups and stronger hydrogen bonds of the C(2) -H groups was supported by Raman results. [224] Lou et al described a simple drop-and-detect method using porous alumina ceramics as platforms for rapid SERS spectroscopy. Their proposed drop-and-detect method was demonstrated in relevant way by the quantitative detection of trace levels of melamine in liquid milk achieving a lowest detectable concentration of 0.1 mg/L, indicating its advantages of simplicity and efficiency for practical SERS applications.…”
Section: New or Emerging Techniquesmentioning
confidence: 99%